Activation of the eis gene in a W-Beijing strain of Mycobacterium tuberculosis correlates with increased SigA levels and enhanced intracellular growth - Wu, Shiping (Microbiology Society, 2009)
There is growing evidence that strains of Mycobacterium tuberculosis differ in pathogenicity and transmissibility, but little is understood about the contributory factors. We have previously shown that increased expression of the principal sigma factor, SigA, mediates the capacity of M. tuberculosis strain 210 to grow more rapidly in human monocytes, compared with other strains. Strain 210 is part of the widespread W-Beijing family of M. tuberculosis strains and includes clinical isolate TB294. To identify genes that respond to changes in SigA levels and that might enhance intracellular growth, we examined RNA and protein expression patterns in TB294-pSigA, a recombinant strain of TB294 that overexpresses sigA from a multicopy plasmid. Lysates from broth-grown cultures of TB294-pSigA contained high levels of Eis, a protein known to modulate host–pathogen interactions. DNA microarray analysis indicated that the eis gene, Rv2416c, was expressed at levels in TB294-pSigA 40-fold higher than in the vector control strain TB294-pCV, during growth in the human monocyte cell line MonoMac6. Other genes with elevated expression in TB294-pSigA showed much smaller changes from TB294-pCV, and the majority of genes with expression differences between the two strains had reduced expression in TB294-pSigA, including an unexpected number of genes associated with the DNA-damage response. Real-time PCR analyses confirmed that eis was expressed at very high levels in TB294-pSigA in monocytes as well as in broth culture, and further revealed that, like sigA, eis was also more highly expressed in wild-type TB294 than in the laboratory strain H37Rv, during growth in monocytes. These findings suggested an association between increased SigA levels and eis activation, and results of chromatin immunoprecipitation confirmed that SigA binds the eis promoter in live TB294 cells. Deletion of eis reduced growth of TB294 in monocytes, and complementation of eis reversed this effect. We conclude that SigA regulates eis, that there is a direct correlation between upregulation of SigA and high expression levels of eis, and that eis contributes to the enhanced capacity of a clinical isolate of M. tuberculosis strain 210 to grow in monocytes.